Evaluation of meningococcal vaccination policies among colleges and universities — United States, 2017. Issue 5 (4th July 2021) - Oliver, Sara E.; Patton, Monica E.; Hoban, Mary; Leino, Victor; Mbaeyi, Sarah A.; Hariri, Susan; MacNeil, Jessica R.
Abstract: Objective Quadrivalent meningococcal conjugate vaccines (MenACWY) have been recommended routinely for adolescents since 2005; in 2015, serogroup B meningococcal (MenB) vaccines were recommended for persons aged 16–23 years based on individual clinical decision making. We surveyed college health providers or administrators to understand current meningococcal vaccine policies. Methods/Participants: In January 2017, we distributed a survey to 985 institutions in partnership with the American College Health Association to assess vaccination policies and outbreak response plans. Results: Overall, 352 (36%) institutions completed the survey. Most either required (N = 186, 53%) or recommended (N = 148, 42%) a meningococcal vaccine; only half (N = 167) had a policy specifically addressing MenB vaccines. Few institutions with a MenB vaccine policy required vaccination (N = 7, 4%); most recommended vaccination (N = 160, 96%). Conclusion: Most institutions have a meningococcal vaccination policy; however, there is substantial diversity in policies. Fewer schools have policies specifically addressing MenB vaccines.